AKTIVITAS ANTIFUNGI MINYAK ATSIRI DAUN KEMANGI (Ocimum x africamum Lour.) TERHADAPTrichophyton rubrum dan Trichophyton mentagrophytes - Annisa Mulia Anasis; Mashuri Yusuf; Sigit Prayoga (JFL : Jurnal Farmasi Lampung, 2021)
Abstract Traditional medicine using natural because it has small side effects and more economical than the synthetic drugs. One of the medicinal plants that for traditional medicine is basil (Ocimum x africamum Lour.).Basil plants contain active compounds such as alkaloids, saponins, flavonoids, triterpenoids, steroids, tannins, eugenol, phenols and essential oils that act as antifungals. Sweet basil essential oil can damage fungal cell membranes so that fungal cell molecules lyse which results in fungal cell death. The purpose of this study was to prove the antifungal activity of sweet basil essential oil as antifungal against T. rubrum and T. mentagrophytes. The essential oil from sweet basil leaves was obtained as much as 18 ml using the steam distillation method. Testing for antifungal activity was carried out using the agar dilution method/well method. The concentrations used in this study were 10%, 20%, 30%, 40%, 100%, positive control using ketoconazole and negative control using aquades with media Potato Dextrose Agar (PDA).Based on the results of research that has been carrier out, basil leaves essential oil has antifungal activity against with the largest inhibition greatest at 100% concentration with an inhibition zone diameter of 15,05 mm for T. rubrum and 19,11 mm for T. mentagrophytes Key words : antifungal, essential oil of sweet basil leaves, Trichophyton rubrum, Trichophyton mentagrophytes